EVALUATION OF SOCIAL COSTS OF DEPENDENT AND INDEPENDENT TRACTION IN RAILWAY FREIGHT TRAFFIC IN SLOVAKIA (Perner's Contacts, 2015)
The paper deals with economic evaluation of the use of dependent and independent traction in rail freight in terms of internal costs, the cost of the infrastructure owner and external costs. Internal cost carrier is calculated in proposed model train by pre-calculation method. The electrical equipment cost of manager of infrastructure is compared with transport performances of freight and passenger railway operators. The paper provides with the results of the survey focused on the comparison of social costs incurred by the use of dependent and independent traction in Slovakia.
Keywords: independent traction, dependent traction, social costs, railway freight transport